The book of Indian birds - Ali, Sálim, 1896-1987 (Mumbai : Bombay Natural History Society , New York : Oxford University Press, 2002)
Preface to the 13th Edition / by J. C. Daniel. --
With 64 plates in colour by carl D´Silva (depicting 538 species) 5 in line and 8 plates of colour photographs.
Mapa de la India en guardas.
Incluye índice.
Bibliografía: página 314.
Keywords: AVES -- INDIA